(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines corporate culture as an important factor in enhancing the motivation of faculty members in higher education institutions. The study analyzes the theoretical foundations of corporate culture and its influence on academic engagement, professional identity, organizational commitment, and job satisfaction. Particular attention is given to the role of shared values, academic recognition, collaboration, leadership, and professional development in strengthening faculty motivation. The findings indicate that a positive corporate culture contributes to increased professional performance, innovation, and continuous learning among academic staff. The study concludes that the development of a strong corporate culture should be considered a strategic priority for ensuring educational quality and sustainable university development.